The problem of slavery in Aristotle - García Mercado, Miguel Ángel (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Aristotle, without a doubt, is one of the greatest geniuses of all time, not only for his philosophical and scientific works, but also for his profound ethical disposition in his writings. In his works he asks the human being to live in accordance with the best that is in him. However, Aristotle is also recognized as one of the defenders of slavery. How can we explain this fact to the contemporary human being? This question requires special attention to the methodological and historical reasons in which Aristotle’s thought is immersed. There are also other deeper reasons that allow Aristotle to justify the existence of men who are slaves by nature, even considering the slave as «a possession with a soul».
Keywords: slavery; possession with a soul; city-state; nature